Stem cell-derived exosomes from human exfoliated deciduous teeth promote angiogenesis in hyperglycemic-induced human umbilical vein endothelial cells - Thanapat SUNARTVANICHKUL; Tawepong ARAYAPISIT; Sujiwan Seubbuk SANGKHAMANEE; Chaiyapol CHAWEEWANNAKORN; Kengo IWASAKI; Phatchanat KLAIHMON; Hathaitip SRITANAUDOMCHAI (University of São Paulo, 2023)
Abstract Objective To investigate the angiogenesis in human umbilical vein endothelial cells (HUVEC) under high glucose concentration, treated with exosomes derived from stem cells from human exfoliated deciduous teeth (SHED). Methodology SHED-derived exosomes were isolated by differential centrifugation and were characterized by nanoparticle tracking analysis, transmission electron microscopy, and flow cytometric assays. We conducted in vitro experiments to examine the angiogenesis in HUVEC under high glucose concentration. Cell Counting Kit-8, migration assay, tube formation assay, quantitative real-time PCR, and immunostaining were performed to study the role of SHED-derived exosomes in cell proliferation, migration, and angiogenic activities. Results The characterization confirmed SHED-derived exosomes: size ranged from 60-150 nm with a mode of 134 nm, cup-shaped morphology, and stained positively for CD9, CD63, and CD81. SHED-exosome significantly enhanced the proliferation and migration of high glucose-treated HUVEC. A significant reduction was observed in tube formation and a weak CD31 staining compared to the untreated-hyperglycemic-induced group. Interestingly, exosome treatment improved tube formation qualitatively and demonstrated a significant increase in tube formation in the covered area, total branching points, total tube length, and total loop parameters. Moreover, SHED-exosome upregulates angiogenesis-related factors, including the GATA2 gene and CD31 protein. Conclusions Our data suggest that the use of SHED-derived exosomes potentially increases angiogenesis in HUVEC under hyperglycemic conditions, which includes increased cell proliferation, migration, tubular structures formation, GATA2 gene, and CD31 protein expression. SHED-exosome usage may provide a new treatment strategy for periodontal patients with diabetes mellitus.